Pengaruh Kegiatan Jumat Rohani terhadap Akhlak Siswa Di SMPN 2 Telukjambe Timur Karawang - Anjani, Jihan Fajira; Nur, Tajuddin; Permana, Hinggil (Peneliti.net, 2024)
Guardians and educators share the responsibility for forming good character and behavior in students, especially for overcoming delinquency in the school environment. Mental health (Spiritual) is an important factor determining good morals so that humans have noble morals. Therefore, to instill moral values ​​in students, the school organizes spiritual Friday activities (jumroh), which are activities that are carried out at the beginning of every month on Friday mornings which have allowances to support Islamic programs that aim to increase faith, understanding, strengthening and practicing Islamic teachings, so that they become Muslims who believe and fear Allah SWT and have a noble mindset. My research focuses on the influence of spiritual Friday activities on student morals carried out by Islamic Religious Education teachers on student morals. The purpose of this research is to describe what spiritual Friday activities (jumroh) are at SMPN 2 Telukjambe Timur Karawang and what are the effects of spiritual friday activities (jumroh) on student morals at SMPN 2 Telukjambe Timur Karawang. The methods used in this study were interviews, observation and library studies.